2002
DOI: 10.1037/h0095020
|View full text |Cite
|
Sign up to set email alerts
|

Measuring practitioners' beliefs, goals, and practices in psychiatric rehabilitation.

Abstract: This article reports on a scale to measure the psychiatric rehabilitation beliefs, goals, and practices of staff who provide services to consumers. The scale's reliability, validity, and factor structure are presented based upon 469 staff members and 191 people in rehabilitation. The scale appears to be a stable measure of staff members' knowledge of modern psychiatric rehabilitation beliefs, goals, and practices as elaborated by the field's leadership. It also appears to provide a valid measure of staff membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 37 publications
(39 reference statements)
1
33
0
Order By: Relevance
“…Nevertheless, staff with PSR degrees did, in fact, express a significantly greater understanding of PSR goals, beliefs and practices as measured by the PRBGP scale than their colleagues who did not have this training. Given that other research has shown that the PRBGP scores are positively associated with desired consumer outcomes (Casper et al, 2002), the present study provided an indirect demonstration that PSR education promotes positive consumer outcomes.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, staff with PSR degrees did, in fact, express a significantly greater understanding of PSR goals, beliefs and practices as measured by the PRBGP scale than their colleagues who did not have this training. Given that other research has shown that the PRBGP scores are positively associated with desired consumer outcomes (Casper et al, 2002), the present study provided an indirect demonstration that PSR education promotes positive consumer outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…It was found to be internally consistent and has an acceptable level of test-retest reliability. Casper et al (2002) conducted a construct validity study in which staff PRBGP scale scores were related to outcome measures of consumer empowerment (Rogers, Chamberlain, et. al.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This scale has established acceptable internal consistency with Cronbach's alphas ranging from .68 to .84 and high test-retest reliability, r tt ¼ .92 (Casper et al, 2002). The instrument assesses a number of factors including beliefs in consumer choice and empowerment, the importance of consumer preferences, the relevance of skills and interests over symptoms, the role of environments and supports, and the differential adaptation of persons with mental illness based on a variety of factors.…”
Section: Psychiatric Rehabilitation Beliefs Goals and Practices Scamentioning
confidence: 98%
“…For example, Casper and colleagues (Casper et al 2002;Casper and Oursler 2003) have developed a scale to measure beliefs and practices related to psychiatric rehabilitation. Similarly, Chinman and colleagues developed a scale to measure attitudes, knowledge, and skills in working with adults with severe mental illness (Chinman et al 2003).…”
Section: Introductionmentioning
confidence: 99%